2011
DOI: 10.1074/jbc.m111.260802
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin 27 Protein Regulates Trafficking of a p21-activated Kinase (PAK) Interacting Exchange Factor (β-Pix)-G Protein-coupled Receptor Kinase Interacting Protein (GIT) Complex via a PDZ Domain Interaction

Abstract: Background: Sorting Nexin 27 regulates intracellular trafficking of proteins through the endosomal system. Results: An interaction between SNX27 and the guanine nucleotide exchange factor ␤-Pix in complex with Git family proteins is identified. Conclusion: Cells lacking SNX27 have decreased cell motility, which we propose to be due to ␤-Pix intracellular trafficking defects. Significance: The results and model proposed have implications for recruitment/activation of p21-activated kinase (PAK) or Rho GTPases at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…SNX27, however, possesses a unique PDZ domain involved in alternative cargo trafficking (Cai et al, 2011;Gallon et al, 2014;Lauffer et al, 2010;Lunn et al, 2007;Steinberg et al, 2013;Temkin et al, 2011;Valdes et al, 2011;Wang et al, 2013), and our results now suggest an additional unique property of this protein with respect to lipid headgroup association, such that it interacts with PtdInsP species not bound by the other family members. Sequence analyses of the PX-FERM proteins highlight positively charged residues found exclusively in SNX27, which are structurally predicted to form a contiguous basic surface on the F3 module, and we find this pocket is required for the differing PtdInsP-binding specificities of the protein.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…SNX27, however, possesses a unique PDZ domain involved in alternative cargo trafficking (Cai et al, 2011;Gallon et al, 2014;Lauffer et al, 2010;Lunn et al, 2007;Steinberg et al, 2013;Temkin et al, 2011;Valdes et al, 2011;Wang et al, 2013), and our results now suggest an additional unique property of this protein with respect to lipid headgroup association, such that it interacts with PtdInsP species not bound by the other family members. Sequence analyses of the PX-FERM proteins highlight positively charged residues found exclusively in SNX27, which are structurally predicted to form a contiguous basic surface on the F3 module, and we find this pocket is required for the differing PtdInsP-binding specificities of the protein.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that the PX domain of these proteins binds with high specificity to PtdIns3P, driving their localization to PtdIns3P-enriched early endosomes Stockinger et al, 2002). PX-FERM proteins can then interact with cargo containing NPxY or NxxY motifs, and also PDZ-binding motif (PDZbm) cargo, in the case of SNX27, at the early endosomal membrane (Balana et al, 2011;Bottcher et al, 2012;Cai et al, 2011;Ghai et al, 2013;Hayashi et al, 2012;Joubert et al, 2004;Knauth et al, 2005;Lauffer et al, 2010;Lunn et al, 2007;Steinberg et al, 2013;Temkin et al, 2011;Valdes et al, 2011;Wang et al, 2013). This influences the routing of transmembrane cargo trafficking, away from degradative late endosomes and into recycling and retrieval pathways from the endosome back to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Two 5Ј-phosphorylated oligonucleotides (AAAGAAACAGTGGAGATATTCAATAAT-AGTGAAGCCACAGATGTATTATTGAATATCTCCACTG-TTGG and AATTCCAACAGTGGAGATATTCAATAA-TACATCTGTGGCTTCACTATTATTGAATATCTCCAC-TGTTT) were annealed and ligated into BbsI and EcoRI-cut pFIV-mCherry. Other constructs used here have been described (17,(53)(54)(55).…”
Section: Methodsmentioning
confidence: 99%
“…3B), consistent with the immunoprecipitation and colocalization studies. We then used well characterized SNX27 mutants (53) to define further the structural elements of the SNX27-PTHR interaction. HEK293 cells stably expressing HA-PTHR were transfected with wild-type SNX27 or with deletion mutants lacking either the PDZ (SNX27⌬PDZ) or FERM (SNX27⌬FERM) domains (Fig.…”
Section: Pthr Interacts With Snx27 In Earlymentioning
confidence: 99%
“…Elucidating the mechanism of receptor sorting mediated by SNX27 will not only further our understanding AMPAR-mediated changes in synaptic plasticity, but may ultimately shed light on the molecular mechanisms that govern learning. membrane (14)(15)(16)(17)(18). The PDZ domain is a protein interaction module recognizing short amino acid motifs found at the C termini of several synaptic targets.…”
mentioning
confidence: 99%